Exploring risk associated to public infrastructure projects case study of Kuala Terengganu Bypass - Nur Haisera, Idris (2019)
This study proposed an empirical study of risk assessment module for public road construction projects. This study employs a case study of a conventional road construction projects for Bypass Kuala Terengganu that has been initiated by the Ministry of Works Malaysia since July 2016. The projects involve the construction of 5.875km route from the state route Tok Molor, Jalan Tok Adis (T12) to Kampng Durian Burung at Federal route (FT03) Kota Bharu-Kuala Terengganu. Seven delay factors and twenty-two sub-factors were designated from a review of literature and consultations with public road experts. The designate pair-wise questionnaire survey was distributed to the road project team in accordance with the Analytic Hierarchy Process (AHP) technique. The delay risk was assessed quantitatively by prioritizing the risk delay factors in determining the critical construction phase. This study identified the top five most prioritized factors as follows: that the most prioritised risk factor in infrastructure projects with respect to goal is technical risk (0.11029), followed by environmental risk (0.23276), project risk (0.34834), and operational is (0.30861). The sub-factors weights were also ranked and the top five sub-factors will be further discussed. The table 4 shows uncertainty of weather (0.73289) as the top risk which is the main caused most of the delay project, followed by land acquisition issues (0.55465), late submission of approved for construction drawing causing delay in in project submission delay (0.39605), the new design does not consider existing drainage system causing flood (0.35202), and unexpected ground condition (0.30084). Therefore, the AHP method can be identified by classification weighted of the most prioritize risk in this project.